Correlates of negative attitudes of undergraduate students - Yildiz, S (Elsevier Ireland Ltd, 2003)
[Abstract Not Available]
3rd Meeting of the European-Academy-of-Forensic-Science -- SEP 22-27, 2003 -- ISTANBUL, TURKEY
Keywords: Homosexuals; Negative Attitudes; Gender